Influence of fermentation liquid from waste activated sludge on anoxic/oxic- membrane bioreactor performance: Nitrogen removal, membrane fouling and microbial community. (February 2018) - Han, Xiaomeng; Zhou, Zhen; Mei, Xiaojie; Ma, Yan; Xie, Zhenfang
Graphical abstract: Highlights: WAS fermentation liquid improved denitrification efficiency in the A/O-MBR. Membrane fouling was increased after fermentation liquid addition. Concentration of proteins and humic acids in bound EPS rose. Changes of deposition rate and fluid structure of SMP and LB-EPS occurred. Fermentation liquid enriched bacterial communities that can secrete EPS. Abstract: In order to investigate effects of waste activated sludge (WAS) fermentation liquid on anoxic/oxic- membrane bioreactor (A/O-MBR), two A/O-MBRs with and without WAS fermentation liquid addition were operated in parallel. Results show that addition of WAS fermentation liquid clearly improved denitrification efficiency without deterioration of nitrification, while severe membrane fouling occurred. WAS fermentation liquid resulted in an elevated production of proteins and humic acids in bound extracellular polymeric substance (EPS) and release of organic matter with high MW fractions in soluble microbial product (SMP) and loosely bound EPS (LB-EPS). Measurement of deposition rate and fluid structure confirmed increased fouling potential of SMP and LB-EPS. γ-Proteobacteria and Ferruginibacter, which can secrete and export EPS, were also found to be abundant in the MBR with WAS fermentation liquid. It is implied that when WAS fermentation liquid was applied, some operational steps to control membrane fouling should be employed.